HUBUNGAN ANTARA PENGGUNAAN ELEMEN GAMIFIKASI DALAM PEMBALAJARAN PENJAS DENGAN KEPUASAN DAN KETERLIBATAN SISWA - Al Hasan, Muhammad Zaidan; Januar Abdilah Santoso (Journal Sport Science, Health and Tourism of Mandalika (Jontak) e-ISSN 2722-3116, 2026)
The use of gamification in Physical Education learning is an innovative strategy that has the potential to improve the quality of students' learning experiences. This study aims to analyze the relationship between the use of gamification elements in Physical Education learning and student learning satisfaction and engagement at Madina Integrated Vocational High School. The study used a quantitative approach with a correlational survey method. The sample consisted of 36 students selected through stratified sampling. The research instrument was a validated and reliable Likert-scale questionnaire. Data were analyzed using descriptive statistics, Pearson correlation tests, and simple linear regression using SPSS software. The results showed that gamification elements had a positive and significant relationship with learning satisfaction (r = 0.640; p < 0.05) and student engagement (r = 0.698; p < 0.05). Furthermore, the regression results indicated that gamification had a positive effect on both variables. The conclusion of this study confirms that the implementation of gamification elements can increase student learning satisfaction and engagement in Physical Education learning. Therefore, gamification is recommended for planned implementation to improve the quality of learning. Keywords: gamification, learning satisfaction, student engagement, physical education